2019
DOI: 10.1016/j.gore.2019.100518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of CNS metastases from primary gynecologic cancers

Abstract: HighlightsMost common symptoms for patients with CNS metastases are headaches and ataxia.Multiple foci are more common than solitary lesions on initial brain imaging.The frontal lobe is most likely to be involved.GTN is diagnosed at a younger age when compared to other gynecologic cancers.More aggressive histologic subtypes confer an increased risk of CNS metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 16 publications
0
21
0
5
Order By: Relevance
“…Atypical sites of metastasis include extra-abdominal lymph nodes, liver, adrenals, brain, bones and soft tissue [6]. Central nervous system (CNS) metastases are generally rare, but in a recent series from University of North Carolina from 2004-2018, 24 cases were identified and 83% of these including 'high grade' (i.e., type 2 histologies) [7]. A preceding Mayo Clinic review of 1,632 endometrial cancer included 18 referred for treatment of brain metastases -those with single site of disease had best prognosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Atypical sites of metastasis include extra-abdominal lymph nodes, liver, adrenals, brain, bones and soft tissue [6]. Central nervous system (CNS) metastases are generally rare, but in a recent series from University of North Carolina from 2004-2018, 24 cases were identified and 83% of these including 'high grade' (i.e., type 2 histologies) [7]. A preceding Mayo Clinic review of 1,632 endometrial cancer included 18 referred for treatment of brain metastases -those with single site of disease had best prognosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1970, 83 papers on the brain parenchymal metastases of CC have been published, including a total of 716 patients ( Table 1 and Table S1 ). In contrast, there are less than 30 cases of leptomeningeal involvement reported in the English literature [ 36 , 81 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. Autopsy studies have reported brain parenchymal metastases in 3–10% of CC patients [ 27 , 57 , 147 ], whereas the estimated frequency in the clinical setting ranged from 0.1% to 2.2% in this review; therefore, we mainly summarized information on brain parenchymal metastases.…”
Section: Cervical Cancermentioning
confidence: 99%
“…The initial symptoms of BMs from CC may be nonspecific, and may include headaches (45.6%), syncope or seizures (14.0%), ataxia (11.8%), nausea/vomiting (11.0%), hemiparesis (10.3%), visual disturbance including diplopia (8.8%), generalized or extremity weakness (8.8%), altered mental status (6.6%), dizziness (5.1%), confusion (5.1%), speech impairment (5.1%), paresthesia, facial twitching, tinnitus, tremor and hemiballismus [ 11 , 14 , 18 , 20 , 21 , 23 , 24 , 25 , 26 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 42 , 43 , 44 , 45 , 47 , 50 , 51 , 52 , 55 , 56 , 57 , 58 , 60 , 61 , 63 , 64 , 65 , 76 , 80 , 81 ]. Intracranial edema resulted in papilledema due to the increased intracranial pressure, which is a common sign of a brain tumor [ 64 , 148 ].…”
Section: Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations